Production and reproduction performance of buffaloes under field conditions in Krishna district of Andhra Pradesh - Rangamma, Batthina; Jagadeeswara Rao, Satyavarapu; M.V.Prasad, Rayavarapu; raghava rao, Elineni (Indian Journal of Dairy Science, 2017)
A study was undertaken on the buffalo production and reproduction characters like Age at first calving, Service period, Calving interval, peak yield, lactation milk yield and dry period in Murrah, graded Murrah and local buffaloes. The average peak yield and lactation milk yield of graded Murrah buffaloes was significantly higher in the urban area than that in semi-urban and rural areas of the study area.Â  However, there was no significant difference in the lactation period of graded Murrah buffaloes in rural, semi-urban and urban areas of the district. The average age at first calving of local buffaloes was significantly lower in urban area than that in semi-urban and rural areas.Â  The average peak yield and lactation milk yield of local buffaloes was significantly higher in the urban and semi-urban areas than that in rural area.